Fog Study at Ardabil Airport for the Statistical Period From 2011 to 2020 - Razieh Pahlavan; Mohammad Moradi; Sahar Tajbakhsh; Majid Azadi; Mehdi Rahnama (Nīvār, 2022)
The presence of fog reduces the horizontal visibility to less than 1000 meters and disrupts air transport services and can make it impossible for aircraft to land and take off. Climatology of fog can help better diagnosis and prediction of fog. In this study, METAR data from 2011 to 2020 were used to detect fog events at Ardebil Airport and according to the classification algorithm of Tardif and Rasmussen (2007), the types of events were determined. Then the fog climate was studied during the period. The results showed that the most common type of fog at Ardebil Airport is radiation fog and the rarest type is precipitation fog. In terms of duration of fog event, radiation fog was the longest fog event and precipitation fog was the shortest fog event. The highest incidence of fog during the study years was at 3 and 4 GMT. The monthly distribution of radiation fog showed that events often occurred in autumn and early winter (September to December). In terms of annual changes in the occurrence of fog, there was no significant trend in the number of fog hours during the studied years, except for the last three years which had a decreasing trend.